Surface Characterization of Helium Plasma Treated Nano-SiO2 Sol-gel Coated UHMWPE Filaments by Contact Angle Experiments and ATR-FTIR (Journal of Fiber Bioengineering and Informatics, 2018)
Ultrahigh molecular weight polyethylene (UHMWPE) Filaments has a low surface free energy and therefore modification of their surface properties before any use is often needed. Atmospheric pressure plasmas treatment is a convenient and environment friendly way to obtain these modifications by introducing new chemical groups at the surface without affecting the bulk properties. This paper studies the influence of nano-SiO_2 Sol-gel coated pretreatment on atmospheric pressure jet (APPJ) treatment of UHMWPE fibers with helium used as the treatment gas. The surface properties of the plasma-treated UHMWPE Filaments are characterized using contact angle measurements and ATR-FTIR spectroscopy. The UHMWPE Filaments show a remarkable increase in surface free energy after plasma treatment. ATR-FTIR spectroscopy of the plasma-treated UHMWPE Filaments reveals that plasma treatment introduces oxygen-containing functionalities, such as ketones, aldehydes, alcohols and carboxylic acids on the UHMWPE Filaments surface leading to the increase of surface free energy.